The effect of oral hygiene instruction on dental plaque removal among selected kindergarten pupils of Lourdes School Quezon City (School Year 1985-1986 - Cheong, John Paul; Go, Susan; Gonzales, Angela (Adviser).
This study provides new information on the effectivity of group instruction on dental plaque removal among kindergarten children from middle income families. It also notes the state of the art one month after instruction without reinforcement. Twenty children aged six were given a single session lecture and demonstration on oral hygiene and the correct method of toothbrushing. Their brushing skills, in terms of plaque removal were recorded before the instruction, one week, two weeks, and four weeks after instruction. Based on this study, the amount of plaque removed increased consistently up to the fourth week post-instruction.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Children -- Dental care; Dental plaque